Scientific, inquiry, and animation integration: The IPSIA learning model in chemistry - Siregar, Rabiyatul Adawiyah; Ndruru, Sun Theo Constan Lotebulo; Lubis, Armansyah; Siregar, Ali Akbar; Siregar, Nurhijriyah Kam (Pascasarjana Universitas Negeri Medan, 2024)
This study addresses the issue of low active participation among students in chemistry learning, as well as their difficulties in understanding macroscopic, microscopic, and symbolic concepts, which contribute to unsatisfactory learning outcomes. To tackle these challenges and enhance students' performance in chemistry, a valid, practical, and effective IPSIA learning model was developed. The research employed a development approach based on the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model, beginning with a thorough analysis of the curriculum. This was followed by the design of the IPSIA model, which was validated using a questionnaire instrument. The results of the validity test scored 98, categorizing it as